In-situ extracellular protein isolation of yarrowia lipolytica through membrane technology: A review - Derek, C. J. C.; Zulkali, M. M. D.; Ahmad, A. L. (2004)
The yeast Yarrowia lipolytica is one of the most intensively studied non-conventional yeast species. They exhibit a remarkable performance in the efficient secretion of various heterologous proteins. The potential of having an in-situ isolation of the proteins would be very much desired since fermentation and product recovery can be carried out simultaneously. Incorporation of membrane technology for such purposes would be beneficial as an initial bulk volume reduction and partial purification. Consideration must be given to membrane as well as the protein as separation may be affected by the MWCO and various interactions possible between solvent, solute and the membrane which would lead to deterioration in efficiency and fouling. Studies related to Y. lipolytica cultivation and in-situ isolation which have been carried out are compiled and configuration of in-situ protein recovery for the yeast is proposed. The prospect for continuous recovery extracellular protein is highlighted.